Prognostic value of post-procedural aPTT in patients with ST-elevation myocardial infarction treated with primary PCI - Kikkert, Wouter J.; van Nes, Sophie H.; Lieve, Krystien V. V.; Dangas, George D.; van Straalen, Jan; Vis, Marije M.; Baan, Jan, Jr; Koch, Karel T.; de Winter, Robbert J.; Piek, Jan J.; Tijssen, Jan G. P.; Henriques, Jose P. (Thrombosis and Haemostasis, 2013)
Unfractionated heparin is the most commonly used anticoagulant in ST-elevation myocardial infarction (STEMI) and its effect can be monitored with activated partial thromboplastin time (aPTT). However, the optimal aPTT range during heparin therapy after primary percutaneous coronary intervention (PCI) is yet to be defined. A mean aPTT was calculated of all aPTT measurements in the first 24 hours after pPCI in a total of 1,876 STEMI patients. Mean aPTT measurements were stratified into four categories; < 1.5 times the upper limit of normal (ULN), 1.5 – 2.0 times ULN (the therapeutic group), 2.01 – 3.99 times ULN, and ≥ 4 times ULN. Compared to patients with a therapeutic aPTT, patients with aPTTs < 1.5 times ULN had no increase in recurrent ischaemic events and had similar rates of bleeding complications. Patients with a mean aPTT ≥ 4 times ULN had higher rates recurrent ischaemic and haemorrhagic complications. After multivariable analyses, aPTT ratios ≥ 4 times ULN were no longer associated with recurrent ischaemic events, but remained a strong predictor of severe and moderate bleeding (hazard ratio [HR] 4.64, p = 0.016 and HR 2.27, p = 0.052). In conclusion, in 1,876 STEMI patients treated with pPCI, low aPTTs in the first 24 hours after PCI were not associated with an increase in ischaemic events, whereas high aPTT values were associated with more frequent bleeding complications. These results indicate no clear benefit as well as a safety concern with heparin treatment after primary PCI.
Keywords: Acute myocardial infarction; heparins; intravascular devices